Effect of grazing frequency of goats on the suppression of three species of plants in the rangeland - Martinez-Ruiz, Edith del Carmen; Guillen-Muñoz, Juan Manuel; Ángel-García, Oscar; Carrillo-Moreno, Dalia Ivette; de Santiago-Miramontes, Ma de los Angeles; Contreras-Villarreal, Viridiana; Véliz-Deras, Francisco Gerardo; Gaytán-Alemán, Leticia (Ecosistemas y Recursos Agropecuarios, 2022)
The aim of the study was to compare the frequency of grazing with goats on the number of plants of three species from a rangeland. The study was carried out in northwestern Mexico (25 N). The treatments consisted of two grazing frequencies, once or twice a week, in an area of 9 m2 in which the species of three species of Solanum eleaegnifolium, Prosopis spp and Salsola Kali plants were found. Grazing was performed during two hours for four weeks. In each sampling area, the population density of each plant was determined. No significantdifferences were observed in the number ofSolanum eleaegnifolium or Prosopis spp lants between treatments or over time (P > 0.05). However, for Salsola Kali, the number of plants decreased significantly (P < 0.05) through the weeks regardless of the treatment (P > 0.05). Therefore, directed grazing with goats against Salsola kali proved to be an effective way to control this species.